Micro-Computed Tomographic Evaluation of the Shaping Ability of Vortex Blue and TruNatomyTM Ni-Ti Rotary Systems - Batool Alghamdi; Mey Al-Habib; Mona Alsulaiman; Lina Bahanan; Ali Alrahlah; Leonel S. J. Bautista; Sarah Bukhari; Mohammed Howait; Loai Alsofi (Crystals)
This study aimed to assess and evaluate the canal shaping ability of two different Ni-Ti rotary systems, Vortex Blue (VB) and TruNatomy (TN), using micro-computed tomography in extracted premolars. A total of 20 extracted bifurcated maxillary first premolars with two separate canals were randomly divided into two groups and prepared with either VB 35/0.04 (Dentsply Maillefer, Ballaigues, Switzerland) or TN Medium 36/0.03 (Dentsply Sirona). Pre- and post-instrumentation micro-CT scans were analyzed to measure the following parameters: percentage of untouched canal surface area, changes in canal surface area, changes in canal volume, structural model index (SMI), changes in canal angulation, changes in dentin thickness, transportation, and centering ability. Statistical analysis was performed with a significance level set at p-value < 0.05. Both VB and TN files showed a significant increase in the basic canal geometry parameters including canal surface area and canal volume. Both file systems showed no significant changes in SMI or dentin thickness after canal instrumentation (p > 0.05). Some degree of canal transportation and a similar centering ability ratio with no significant difference were observed in both file systems (p > 0.05). TN files showed less pre-cervical dentin removal when compared to VB files. A significant difference was found in the TN group regarding the dentin removal between coronal and apical thirds (p = 0.03). Both VB and TN files produced comparable root canal preparation with no considerable shaping mishaps and errors. Both files showed minimum canal transportation and minimum straightening of the canal curvature. TN files removed less pre-cervical dentin than apical dentin.